РАСПРЕДЕЛЕНИЕ ПЛОТНОСТИ ПОВЕРХНОСТНЫХ ЗАРЯДОВ НА ГРАНИЦЕ РАЗДЕЛА КОНТАКТИРУЮЩИХ ИЗОЛИРОВАННЫХ ПРОВОДНИКОВ КАБЕЛЕЙ - Беспрозванных, А.В.; Бойко, А.М. (Інститут електродинаміки НАН України, Київ, 2014)
It has been obtained the analytical solution for the density estimation of surface charges which are located on the interface between contacted isolated cables’ conductors by taking into account the skin of impurities and air gap. Distribution of density of charges taking into account change of an electrostatic charge and relative dielectric permeability of a defective layer is presented. It is shown, that the account of change of parameters of a superficial skin during the of ageing of polymeric isolation leads to essential growth of density of surface charges concerning initial, not aging, conditions. References 10, table 1, figures 4.